Perspektif Peran Dinas Sosial Jawa Timur Ditinjau dalam Pemberian Izin Private Adoption - Sheila Puspaningrum (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Direct adoption (private adoption) is the process of adopting a child without an institutional intermediary, whereby the adoption is carried out by a family or specific party. There are requirements and stages that must be passed in order to obtain permission as stated in the applicable regulations. The party responsible for granting direct adoption permission in East Java is the East Java Social Service. This study aims to analyze and describe the role of the East Java Social Services Agency in granting direct adoption permits as seen in Minister of Social Affairs Regulation No. 110/HUK/2009 concerning Adoption Requirements. This study uses a qualitative descriptive method with purposive sampling as the technique for determining informants. The results of the study show that two of the factors, namely the role of the East Java Provincial Social Service as the Provincial Child Adoption Permit Review Team and as the party responsible for issuing child adoption permits, have in principle been carried out effectively and in accordance with applicable regulatory provisions. However, in terms of eligibility assessment, particularly in fulfilling administrative requirements, more comprehensive optimization is still needed. This is due to the limited detailed information received by applicants regarding the procedures and documents that must be fulfilled, which causes various difficulties in preparing the files.